2022
DOI: 10.5194/hess-2022-48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studying the dynamic of a high alpine catchment based on multiple natural tracers

Abstract: Abstract. Hydrological processes in high elevation catchments are largely influenced by snow accumulation and melt, as well as summer rainfall input. The use of the stable isotopes of water as a natural tracer has become popular over recent years to characterize water flow paths and storage in such environments, in conjunction with electric conductivity (EC) and water temperature measurements. In this work, we analyzed in detail the potential of year round samples of these natural tracers to characterize hydro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous hydrological research in the VdN Alpine watershed has shown, through combined piezometer network, thermal imaging from an uncrewed airborne vehicle, isotope analysis and hydrological modeling (Michelon et al., 2022; Thornton et al., 2022), that substantial groundwater release takes place in the VdN throughout Reach 3 (Figure 1b), where almost simultaneous bedload transport waves were measured in some instances between sensors spaced hundreds of meters away (e.g., S12 → S14, S14 → S17). Local hydrological conditions (e.g., notably associated with vertical hyporheic fluxes) may locally reduce the critical shear stress required for entrainment, and may increase sediment mobilization and transport capacity independently from the downstream propagation of the water wave, translating into simultaneous bedload transport mobilized at different locations of the watershed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous hydrological research in the VdN Alpine watershed has shown, through combined piezometer network, thermal imaging from an uncrewed airborne vehicle, isotope analysis and hydrological modeling (Michelon et al., 2022; Thornton et al., 2022), that substantial groundwater release takes place in the VdN throughout Reach 3 (Figure 1b), where almost simultaneous bedload transport waves were measured in some instances between sensors spaced hundreds of meters away (e.g., S12 → S14, S14 → S17). Local hydrological conditions (e.g., notably associated with vertical hyporheic fluxes) may locally reduce the critical shear stress required for entrainment, and may increase sediment mobilization and transport capacity independently from the downstream propagation of the water wave, translating into simultaneous bedload transport mobilized at different locations of the watershed.…”
Section: Discussionmentioning
confidence: 99%
“…A small debris-covered glacier (Glacier des Martinets) occupies ∼3% of the watershed (in 2020), supplying only negligible amounts of ice melt. Thus, the hydrological regime of the watershed is dominated by snowmelt and rainfall (Antoniazza et al, 2022;Ceperley et al, 2020;Mächler et al, 2021;Michelon et al, 2021Michelon et al, , 2022Thornton et al, 2021Thornton et al, , 2022.…”
Section: Study Sitementioning
confidence: 99%
“…Two high-elevation catchments among the 22, namely Dischmabach (DIS) and Ova da Cluozza (OVA), were also investigated in previous studies for climate change impact predictions, low-flow analysis and for understanding the role 120 of quaternary deposits and groundwater in their hydrological functioning (Addor et al, 2014;Staudinger and Seibert, 2014;Staudinger et al, 2015;Jenicek et al, 2018;Arnoux et al, 2021). Among the catchments analyzed by Ceperley et al (2020), the reader is referred to Michelon et al (2022) for further information about the tracer-based dynamics of the Vallon de Nant (VdN) catchment and to Carturan (2016), Carturan et al (2013Carturan et al ( , 2014Carturan et al ( , 2016Carturan et al ( , 2019, Zuecco et al (2019) for glaciological, hydrological and meteorological information about the Noce Bianco at Pian Venezia (NBPV) 125 catchment. Additional details for the dolomitic Bridge Creek Catchment (BCC) are available in the work of Zuecco et al (2018Zuecco et al ( , 2019, Guastini et al (2019) and Penna et al (2016Penna et al ( , 2017.…”
Section: 1mentioning
confidence: 99%